(untitled) (Praxis Educativa, 2024)
This paper addresses the curricular reform of initial teacher training in the City of Buenos Aires, Argentina through the analysis of the single draft for curricular guidelines for initial teacher training promulgated by the Ministry of Education of the jurisdiction in December 2022. First, it provides a contextual analysis of the jurisdictional education policy in the framework of which the mandatory levels of the training system have been changed since 2007. Secondly, it offers an examination of the curricular document referred to from three vantage points: 1) the direct relationship between educational outcomes and teacher empowerment, 2) the dislocation of the disciplinary organization by the focus on socio-emotional skills, and 3) the virtualization of teacher training contents through virtual environments or platforms. Finally, it systematizes the tensions between the democratization of Higher Education and the consecration of these prescriptions.